Health and tuberculosis systems resilience, the role of the private sector and pandemic preparedness: insights from a cross-country qualitative study with policy-makers in India, Indonesia and Nigeria - Madhukar Pai; Poshan Thapa; Charity Oga-Omenka; Angelina Sassi; Vijayashree Yellappa; Petra Heitkamp; Bony Wiem Lestari; Surbhi Sheokand; Nathaly Aguilera Vasquez; Laura Jane Brubacher; Bolanle Olusola-Faleye; Joel Shyam Klinton (BMJ Global Health)
Introduction The COVID-19 pandemic was an unprecedented challenge to health systems worldwide and had a severe impact on tuberculosis (TB) case notifications and service delivery. India, Indonesia and Nigeria are high TB-burden countries where the majority of initial care-seeking happens in the private health sector. The objectives of this study were to (1) explore policy-makers’ perspectives on the impact of the COVID-19 pandemic on private sector TB service delivery in India, Indonesia and Nigeria and (2) identify cross-cutting insights for pandemic preparedness with respect to TB service delivery.Methods From May to November 2021, 33 interviews were conducted with key policy-makers involved in health service administration, TB service delivery and/or the COVID-19 response in India, Indonesia and Nigeria (n=11 in each country). Interviews focused on the impact of COVID-19 on TB services and lessons learnt for pandemic preparedness with respect to TB in each study context. Data were analysed thematically using a hybrid inductive-deductive approach, informed by Haldane et al’s Determinants of Health Systems Resilience Framework.Results Policy-makers highlighted the crucial role of intersectoral collaboration, effective governance, innovative financing strategies, health workforce reallocation and technological advancements such as virtual consultations and mHealth in strengthening TB service delivery amid the COVID-19 pandemic. India relied on patient–provider support agencies to implement a joint strategy for TB care across sectors and states. Indonesia engaged networks of private provider professional associations to facilitate coordination of the COVID-19 response. Nigeria implemented a pandemic policy for public–private referral for the continuity of TB care.Conclusions Countries implemented varied measures to support TB service delivery during the COVID-19 pandemic. This study presents insights from three countries (India, Indonesia and Nigeria) that together offer a ‘menu’ of possibilities for supporting pandemic preparedness with respect to TB care vis-à-vis strengthening health systems resilience.